The Effectiveness of Differential Supervision - Harris, Patricia M. (Crime & delinquency, 2004)
This article presents an evaluation of the Client Management Classification System (CMC), a method for assessment and differential supervision of offenders that embodies the principle of responsivity. As in prior evaluations of the CMC, probationers whose officers were trained in CMC techniques experienced lower rates of revocation compared with regularly supervised subjects. However, the experimental group incurred similar or higher rates of rules violations and arrests. Of particular interest, the study found that supervision of experimental subjects did not conform to recommended CMC strategies. In combination, these results suggest the possibility that training in CMC successfully heightened officers 'understanding of offender motivations and needs, leading them to view probationer misconduct in a more lenient and flexible contextαand thereby producing the appearance of favorable outcomes. The findings have implications for the design of evaluations of efforts to implement principles of effective offender treatment in community corrections agencies. [ABSTRACT FROM AUTHOR]